Greek Fiscal Policy in Times of Crisis: A New Proposed Framework - Vousinas, Georgios L. (HAPSc Policy Briefs Series, 2020)
The present article aims to shed light on the critical matter of overcoming the existing Greek sovereign debt crisis, a crisis that brought to the surface the chronic structural problems of the Greek economy and the long-standing state distortions, by highlighting the importance of a sound and efficient fiscal policy administration model. The author identifies the problematic issues in the current fiscal policy procedures and proposes a new framework so as for the Greek economy to overcome the ongoing crisis and return to positive growth rates, while achieving sustainable growth, a perquisite for socioeconomic welfare. The overall target of this paper is to set the required fiscal policy mix so as for Greek economy to overcome current and future crises and hopefully initiate a fruitful discourse on the subject among all the involved parties.